2013
DOI: 10.1016/j.mcn.2013.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms underlying activity-dependent AMPA receptor cycling in retinal ganglion cells

Abstract: On retinal ganglion cells (RGCs) transmit light encoded information to the brain and receive excitatory input from On cone bipolar cells (CBPs). The synaptic CBP input onto On RGCs is mediated by AMPA-type glutamate receptors (AMPARs) that include both those lacking a GluA2 subunit, and are therefore permeable to Ca2+, and those that possess at least one GluA2 subunit and are Ca2+-impermeable. We have previously demonstrated in electrophysiological studies that periods of low synaptic activity, brought about b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 42 publications
0
7
0
1
Order By: Relevance
“…We have previously shown that ON, but not OFF type RGCs mobilize internal CP-AMPARs for insertion to the surface via both homeostatic and NMDAR dependent mechanisms (Xia et al, 2007 ; Jones et al, 2012 ; Casimiro et al, 2013 ), and we wondered whether ON alpha RGCs labeled in the Opn4 line might similarly maintain a constant number of surface CP-AMPAR by removal and sequestration of excess receptors into an intracellular pool. To test this, AMPA currents were first recorded in the presence and absence of 100 μM PhTX to estimate the size of the surface pool of CP-AMPARs.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that ON, but not OFF type RGCs mobilize internal CP-AMPARs for insertion to the surface via both homeostatic and NMDAR dependent mechanisms (Xia et al, 2007 ; Jones et al, 2012 ; Casimiro et al, 2013 ), and we wondered whether ON alpha RGCs labeled in the Opn4 line might similarly maintain a constant number of surface CP-AMPAR by removal and sequestration of excess receptors into an intracellular pool. To test this, AMPA currents were first recorded in the presence and absence of 100 μM PhTX to estimate the size of the surface pool of CP-AMPARs.…”
Section: Resultsmentioning
confidence: 99%
“…Changes in the composition of AMPARs and trafficking of their subunits may lead to changes in synaptic transmission in the retina (Casimiro et al . ; Henley and Wilkinson ) and changes in escape responses (smaller tail velocities and aberrant turning directions) (Roy et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Several downstream mechanisms might produce this plasticity. First, exocytosis of AMPARs onto dendritic membranes and/or movement of AMPARs from extra-synaptic to synaptic sites may be involved (Casimiro et al, 2013). Second, Ca 2+ influx through CP-AMPARs can trigger a Ca 2+ -dependent phosphorylation of CP-AMPARs (Guire et al, 2008; Kristensen et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In mammalian ON-type ganglion cells an activity-dependent process of “constitutive cycling” of AMPARs has been described (Casimiro et al, 2013). This process involved the cycling of extrasynaptic GluA2-containing (Ca 2+ -impermeable) AMPARs, but not synaptic AMPARs.…”
Section: Introductionmentioning
confidence: 99%